2018
DOI: 10.1515/sjpain-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Exercise does not produce hypoalgesia when performed immediately after a painful stimulus

Abstract: Abstract Background and aims: Exercise-induced hypoalgesia (EIH) and conditioned pain modulation (CPM) are assumed to reflect descending pain inhibition. Potential interactions between EIH and CPM may be important in the therapy of chronic pain, as reduced CPM and increased pain after exercise are frequently observed. This study compared the EIH response after CPM was activated using a cold pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
2
24
1
3
Order By: Relevance
“…The relative test-retest reliability of the hypoalgesic response after walking in this current study shows comparable ICCs to what has been demonstrated previously in studies investigating the test-retest reliability of the EIH responses after high intensity aerobic exercise [13], moderate aerobic exercise [37] and isometric wall squat [14]. Moreover, the relative reliability of EIH across different sessions is comparable to the reliability of the CPM response [38] that may be partly responsible for the EIH response [2,16,17]. It has been suggested that a high focus on standardizations of test protocols and action to prevent assessor bias would increase reliability in test-retest investigations [39].…”
Section: Test-retest Reliabilitysupporting
confidence: 87%
See 1 more Smart Citation
“…The relative test-retest reliability of the hypoalgesic response after walking in this current study shows comparable ICCs to what has been demonstrated previously in studies investigating the test-retest reliability of the EIH responses after high intensity aerobic exercise [13], moderate aerobic exercise [37] and isometric wall squat [14]. Moreover, the relative reliability of EIH across different sessions is comparable to the reliability of the CPM response [38] that may be partly responsible for the EIH response [2,16,17]. It has been suggested that a high focus on standardizations of test protocols and action to prevent assessor bias would increase reliability in test-retest investigations [39].…”
Section: Test-retest Reliabilitysupporting
confidence: 87%
“…The painful CPM paradigm show similar widespead hypoalgesic manifestations as seen for exercise [2], and exercises that consistently produce hypoalgesia is often percieved as moderately painful [13,14]. Moreover, studies have shown larger hypoalgesic responses after painful exercise compared with non-painful exercise [15], and several studies have shown a positive association between the CPM response and the EIH response [2,16,17] suggesting that subjects with reduced CPM have less effect from exercise.…”
Section: Introductionmentioning
confidence: 84%
“…The current findings of a decreased CPM effect after exercise corresponds with a recent study demonstrating that CPM is decreased subsequent to exercise (Alsouhibani et al., ). Gajsar et al., suggested that if CPM and EIH share similar descending pain inhibitory mechanisms, further subsequent CPM effect may not be possible due to a ceiling effect (Gajsar et al., ). As the effect of CPM is thought to be short‐lived (Kennedy, Kemp, Ridout, Yarnitsky, & Rice, ), it is unclear if this could have had an influence the current study design.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the current study the EIH effect detected was small and not consistent across outcomes. The magnitude of the EIH effect has recently been shown to be diminished when evaluated after a CPM paradigm (Gajsar et al, 2018) which may have influenced the possibility to detect EIH in the current study. Furthermore, it is unknown if patients have a similar EIH response, as the majority of research has been on healthy individuals (Koltyn.F, 2000).…”
Section: Exercise-induced Hypoalgesiamentioning
confidence: 93%
See 1 more Smart Citation